COVID-19 and Mitochondrial Non-Coding RNAs: New Insights From Published Data - Pozzi, Andrea (Frontiers in Physiology, 2022)
Scientists all around the world are working to investigate new ways to prevent and treat COVID19, and recent research has been focusing on the effects of a syndrome commonly called ‘long COVID’. People affected by this syndrome usually suffer from symptoms like the ones observed in several types of fatigue syndrome. As these syndromes are often linked to mitochondrial dysfunction, researchers hypothesized that a dysfunction in the mitochondrial metabolism might be part of the causes of long COVID. However, while there are a few studies investigating the effect of SARS-CoV-2 infection on mitochondrial metabolism, the effect on the transcription of mitochondrial non-coding RNAs has not been investigated yet. Thus, using publicly available data, I explored the effect of SARS-CoV-2 on the expression of several mitochondrial non-coding RNAs in patients recovering from COVID19. No change in the expression of long non-coding RNAs was detected at any stage of the infection, but up to 43 small mitochondrial RNAs have their expression altered during the recovery from COVID19. This result suggests that the SARS-CoV-2 infection somehow affected the metabolism of small mitochondrial RNAs specifically without altering the overall mitochondrial transcription. Despite these being only preliminary results on a small cohort, the analyses clearly showed that individuals infected by SARS-CoV-2 retain an altered expression of these small RNAs. This persistent alteration in the expression of small mitochondrial RNAs might be involved in the long COVID syndrome and further studies are needed to confirm the possibility.